Biogas user perceptions of biogas development in Urutsewu Village, Ampel District, Boyolali Regency - Solikah, Anisa Rahmawati; Rifo Nur Laksana Restu; Indriani, Vivi (Talenta Publisher, 2025)
Biogas is an innovation that is already known among livestock farmers. Urutsewu Village uses biogas in an effort to meet energy needs derived from cow dung, chicken dung, tofu liquid waste, and kitchen waste. The purpose of this study was to analyze the perceptions of biogas users towards the installation, economic impact, environmental impact, and social impact of biogas installation in Urutsewu Village. This research was a descriptive research with data collection conducted through direct interviews with biogas users. The source of information data was obtained from 48 respondents consisting of households that own biogas digesters and households that use non-owners of biogas digesters. The results of the study showed that 67% of biogas users knew about biogas before using it and 33% after using biogas. Respondents tended to say that biogas technology is easy to implement, easy and simple maintenance. The perception of biogas users regarding environmental impacts is that biogas technology can reduce pollution, reduce sources of disease and improve environmental quality. Biogas technology can relatively save fuel costs and is cheaper than other fuels but is not sufficient as cooking fuel. The community agrees to process waste into biogas and supports the government in biogas processing